2017
DOI: 10.1016/j.rser.2017.02.075
|View full text |Cite
|
Sign up to set email alerts
|

Impact of operation strategies of large scale battery systems on distribution grid planning in Germany

Abstract: Due to the increasing penetration of fluctuating distributed generation electrical grids require reinforcement, in order to secure a grid operation in accordance with given technical specifications. This grid reinforcement often leads to over-dimensioning of the distribution grids. Therefore, traditional and recent advances in distribution grid planning are analysed and possible alternative applications with large scale battery storage systems are reviewed. The review starts with an examination of possible rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 102 publications
0
69
0
5
Order By: Relevance
“…Therefore, control strategies that minimize those losses and maximize self-consumption are needed. Alternative strategies than a fixed feed-in limit prevent injection peaks are described in [17,18,14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, control strategies that minimize those losses and maximize self-consumption are needed. Alternative strategies than a fixed feed-in limit prevent injection peaks are described in [17,18,14].…”
Section: Introductionmentioning
confidence: 99%
“…Only two of the surveyed DSOs indicated that they already have installed more than 100 voltage-regulated local distribution transformers. 6 In terms of percentage, this translates into a maximum of 1e2% of all local distribution transformers in use in the respective grid areas. These two DSOs stated that for certain cases the voltage-regulated local distribution transformer is the most economical option.…”
Section: Voltage-regulated Local Distribution Transformersmentioning
confidence: 99%
“…They entail for example the implementation of large-scale battery systems [6,10], the control of demand-side appliances like electric vehicles [8,9], or the active power curtailment of PV systems [7,9,10]. According to the interviewed DSOs, these options are however not (yet) economically and/or technically viable.…”
Section: Mitigation Measures For Voltage Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of future grids requires political and regulatory support and the reconstruction of energy generation, market and usage. The German energy storage market is analyzed and the operation strategies of the two most profitable applications, self-consumption maximization and primary frequency control are described by Rescha et al (2017). Haidar et al (2015) review SG system in some states in Australia, and offer some examples on SG at distribution level dealing with interconnection of distributed generation and active distribution management.…”
Section: Introductionmentioning
confidence: 99%